Description of money Waqf Program Management in Indonesia - Muhammad Miqdad Alfarisy; Firmansyah Firmansyah (Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to discuss the description of cash waqf management in Indonesia, from regulations to concepts and strategies for developing cash waqf in Indonesia. This type of research uses a qualitative descriptive method using literature study data. The result of this research is that the implementation of regulations on cash waqf management institutions has been stated in Law number 41 of 2004, part 10, article 28 and Government Regulation (PP) Number 25 of 2018 and Regulation of the Indonesian Waqf Board (BWI) Number 20 of 2020. As for the concepts and strategies that must be carried out by nadzir waqf money, it is regulated that they must pay attention to 2 aspects. First, the security aspect, the second aspect of usability. Problems in managing cash waqf include the large number of nadzir cash waqf which is not transparent and accountability. The finding of cash waqf so that the potential and realization of cash waqf in Indonesia is still not as expected